2012
DOI: 10.2174/187152012798764732
|View full text |Cite
|
Sign up to set email alerts
|

New Targeted Therapies for Anaplastic Thyroid Cancer

Abstract: Anaplastic thyroid cancer (ATC) is often incurable because it doesn't respond to radioiodine, radiotherapy or chemotherapy, and new therapeutic approaches are needed. Peroxisome proliferator-activated receptor-gamma (PPARg) gene and protein are present in ATC cells, and PPARg ligands inhibit cell proliferation, induce apoptosis, and also down regulate the invasive potential of ATC cells. Also, inhibitors of the Aurora serine/threonine kinases have antineoplastic effect on ATC cells in vitro and on ATC xenograf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
3

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 0 publications
1
22
0
3
Order By: Relevance
“…In addition, besides type I and Type II interferons which were previously shown to inhibit the secretion of CXCL8 [13,15], other potentially interesting molecules to be tested for their CXCL8 inhibiting effects could include PPAR-c agonists. This appears to be supported by the evidences provided by Antonelli et al who reported that PPAR-c agonists display antineoplastic activity [25,26] and inhibit the secretion of several chemokines in primary cultures of thyroid cancer cells [27,28]. With specific regards to CXCL8, pioglitazone (a potent PPAR-c agonist) was demonstrated to inhibit the TNF-a induced CXCL8 secretion in endometriotic stromal cells [29] and to suppress CXCL8 mRNA expression in pancreatic cancer cell lines [30].…”
Section: Discussionmentioning
confidence: 65%
“…In addition, besides type I and Type II interferons which were previously shown to inhibit the secretion of CXCL8 [13,15], other potentially interesting molecules to be tested for their CXCL8 inhibiting effects could include PPAR-c agonists. This appears to be supported by the evidences provided by Antonelli et al who reported that PPAR-c agonists display antineoplastic activity [25,26] and inhibit the secretion of several chemokines in primary cultures of thyroid cancer cells [27,28]. With specific regards to CXCL8, pioglitazone (a potent PPAR-c agonist) was demonstrated to inhibit the TNF-a induced CXCL8 secretion in endometriotic stromal cells [29] and to suppress CXCL8 mRNA expression in pancreatic cancer cell lines [30].…”
Section: Discussionmentioning
confidence: 65%
“…In light of its rapid growth rate, it is somewhat surprising that ATC is not sensitive to any current systemic therapies, including radiation or chemotherapy. Although several promising targeted therapies (2)(3)(4)(5) and multimodal treatment strategies (6,7) have been explored, to date no therapy has been definitively proven to prolong survival in these patients. Clearly, novel treatments are desperately needed.…”
Section: Introductionmentioning
confidence: 99%
“…It binds to peroxisome proliferator responsive element (PPRE) as a heterodimer with the retinoid X receptor. The activity or/and expression of PPARγ is downregulated in thyroid cancer (Aldred et al, 2003;Antonelli et al, 2012;Espadinha et al, 2009), suggesting that the defect in PPARγ may contribute to the development of thyroid cancer. Indeed, in a mouse model PPARγ insufficiency results in the activation of the nuclear factor-kappaB (NF-κB) signaling pathway, leading to thyroid carcinogenesis (Kato et al, 2006).…”
Section: Introductionmentioning
confidence: 99%